2019
DOI: 10.3390/su11061622
|View full text |Cite
|
Sign up to set email alerts
|

The Sustainability Performance of Chinese Banks: A New Network Data Envelopment Analysis Approach and Panel Regression

Abstract: This paper develops a new network data envelopment analysis (DEA) model that simultaneously integrates the non-convex metafrontier and undesirable outputs and which is super efficient at performing dynamic network slacks-based measures. The model is employed to discuss the efficiency of 36 commercial banks in China during the years 2010–2014. The efficiency of these banks shows significant heterogeneity and the efficiency of most foreign banks has much room for improvement. Regarding both the non-convex metafr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 66 publications
1
11
0
Order By: Relevance
“…Second, and similar to other studies (Alhassan and Biekpe, 2016; Shim, 2017; Yu et al , 2019; Balsmeier and Czarnitzki, 2017; Schmalz, 2018), this study's results demonstrated that organizational structures and corporate governance are influential in technical efficiency. In the second stage, we observe that the drivers for firm size, reinsurance rate, claim ratio and equity restriction are important determinants of an insurance firm's efficiency.…”
Section: Conclusion and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Second, and similar to other studies (Alhassan and Biekpe, 2016; Shim, 2017; Yu et al , 2019; Balsmeier and Czarnitzki, 2017; Schmalz, 2018), this study's results demonstrated that organizational structures and corporate governance are influential in technical efficiency. In the second stage, we observe that the drivers for firm size, reinsurance rate, claim ratio and equity restriction are important determinants of an insurance firm's efficiency.…”
Section: Conclusion and Discussionsupporting
confidence: 89%
“…In this paper, 44 Chinese property insurance companies in 2017 were selected as the research objects, and technical efficiency was taken as the dependent variable. Previous literature had shown that company size (Li et al , 2017; Yu et al , 2019), loss ratio (Alhassan and Biekpe, 2016), reinsurance ratio (Alhassan and Biekpe, 2016), leverage ratio (Huang and Eling, 2013; Lu et al , 2014), premium growth rate (Shim, 2017) and market share (Ansah-Adu et al , 2012; Choi and Weiss, 2005) had a certain impact on the operating efficiency of enterprises. However, relevant studies did not indicate the relationship between the causes and effects.…”
Section: Fuzzy-set Qualitative Comparative Analysismentioning
confidence: 99%
“…Presently, the DEA method is very popular in banking and financial sector performance measurement. A plethora of studies (e.g., Chang, Jang, Li, & Kim, 2017;Yu, Huang, and Shao, 2019;Sathye, 2003, Ray, 2007Ray and Das, 2010;Hada, Zhu, & Tamang, 2017;Wanke, Barros and Emrouznejad, 2016;Miller and Noulas, 1996;Zhu, Liu, Emrouznejad and Huang, 2017) applied the DEA models in banking and financial sectors of different regions of the world.…”
Section: Bbc Modelmentioning
confidence: 99%
“…Some other studies focused on the evaluation of competitive conditions or market power in the Chinese banking industry [12][13][14], while this paper opens a new area in the investigation of the Chinese banking industry by assessing the redundancy of bank branches. In the sustainable development of commercial banks, several studies focused on the sustainable development model of banks [15][16][17], some on the performance evaluation of sustainable banks [18][19][20][21], and others on the corporate social responsibility of commercial banks [2,3], but this paper studies the sustainable operation of commercial banks from a new perspective of optimizing the layout of bank branches to reduce the operation cost. Optimizing the layout of existing physical branches and allocating resources reasonably and effectively have become the key issues in promoting the sustainable operation of commercial banks in the context of third-party payment, and help commercial banks fulfill corporate social responsibility earnestly.…”
Section: Literature Reviewmentioning
confidence: 99%